Ultrasound Image Quality Comparison Between a Handheld Ultrasound Transducer and Mid-Range Ultrasound Machine - Nayema Salimi; Antonio Gonzalez-Fiol; David Yanez; Kristen Fardelmann; Emily Harmon; Katherine Kohari; Sonya Abdel-Razeq; Urania Magriples; Aymen Alian (POCUS Journal, 2022)
Objectives: Not all labor and delivery floors are equipped with ultrasound machines which can serve the needs of both obstetricians and anesthesiologists. This cross-sectional, blinded, randomized observational study compares the image resolution (RES), detail (DET), and quality (IQ) acquired by a handheld ultrasound, the Butterfly iQ, and a mid-range mobile device, the Sonosite M-turbo US (SU), to evaluate their use as a shared resource.  Methods: Seventy-four pairs of ultrasound images were obtained for different imaging purposes: 29 for spine (Sp), 15 for transversus abdominis plane (TAP) and 30 for diagnostic obstetrics (OB) purposes. Each location was scanned by both the handheld and mid-range machine, resulting in 148 images. The images were graded by three blinded experienced sonographers on a 10-point Likert scale.  Results: The mean difference for Sp imaging favored the handheld device (RES: -0.6 [(95% CI -1.1, -0.1), p = 0.017], DET: -0.8 [(95% CI -1.2, -0.3), p = 0.001] and IQ: -0.9 [95% CI-1.3, -0.4, p = 0.001]). For the TAP images, there was no statistical difference in RES or IQ, but DET was favored in the handheld device (-0.8 [(95% CI-1.2, -0.5), p < 0.001]). For OB images, the SU was favored over the handheld device with RES, DET and IQ with mean differences of 1.7 [(95% CI 1.2, 2.1), p < 0.001], 1.6 [(95% CI 1.2, 2.0], p < 0.001] and 1.1 [(95% CI 0.7, 1.5]), p < 0.001), respectively.  Conclusions: Where resources are limited, a handheld ultrasound may be considered as a potential low-cost alternative to a more expensive ultrasound machine for point of care ultrasonography, better suited to anesthetic vs. diagnostic obstetrical indications.